Perfil clínico, eletrocardiográfico, enzimático, ecocardiográfico e histológico no infarto agudo do miocárdio: estudo experimental em cães - Guilherme Albuquerque de Oliveira Cavalcanti (2010)
Ischemic events in dogs are uncommon, however this may be under-reported. The myocardial infarction was created by left anterior descending coronary ligation in six mongrel dogs, age between 1,5 to 6 years, mean weight of 10,95 ± 3,4 kg, healthy in clinical and laboratorial exams. These dogs were evaluated by clinically, electrocardiography (ECG), ambulatory electrocardiography (AE), echocardiography (ECO), creatine kinase enzyme (CK), creatine kinase MB fraction enzyme (CK-MB) and histopathologically. The animals exhibit left ventricular chamber enlargement and increase in myocardial performance index at ECO. In ECG, there were deviation in ST segment in the precordial leads V1 and V2. The CK and CK-MB showed high increase, the CK and CK-MB peaks occurred six and 12 hours after infarct, respectively. Histopathology the infarction of the inferior wall of the left ventricle and replacement of muscle tissue by fibrous tissue were seen. Furthermore, intramyocardial injection was evaluated by AE, which demonstrated no increase in the ventricular arrhythmias